White workers' grievances and the industrial colour bar 1902-1913 - Katz, Elaine N. (My University, 1975)
After the general strike of July 1913 on the Witwatersrand the Transvaal trade unions (most of which were craft unions) under the auspices of the Transvaal Federation of Trade Unions presented a statement of their grievances in a document entitled “The Workers’ Charter”. These reveal that white workers, particularly mineworkers, had deep-seated grievances. There were precedents for all their demands, and “The Workers' Charter” could have been, a document drafted by trade unionists anywhere in the world. Some of these demands however reveal the major unstated aim, that of preventing non-white encroachment in skilled, semiskilled and even unskilled occupations (1). … The objects of this paper are to try to assess mineworkers’ grievances in 1913 by an analysis of ‘The Workers' Charter’ ; and also to indicate that the Chamber of Mines, although it was opposed to the legal colour bar, helped to perpetuate the colour bar through its low wage policy for Africans.(6)
African Studies Seminar series. Paper presented August 1975
Keywords: Miners. South Africa. Transvaal. History; Industrial relations. South Africa. Transvaal. History; Labor unions. Miners. South Africa. Transvaal. History; Transvaal (South Africa). Race relations